Pengaruh Current Ratio terhadap Return on Assets pada Bumdesa Lancang Kuning Desa Rumbai Jaya Kecamatan Kempas Kabupaten Indragiri Hilir Riau - Suharmiyati Suharmiyati; Yenny Iskandar (Universitas Batanghari, 2020)
This research is done in BUMDesa Lancang Kuning village Rumbai Jaya Kempas Sub-district of Indragiri Hilir. This research aims to determine the influence of current ratio of return on assets on Bumdesa Lancang Kuning village of Tassel Jaya Kempas District of Indragiri Hilir Bumdesa Lancang kuning Village Tassel Jaya Kempas Sub District Indragiri Hilir is a state-owned business entity that aims to improve the economy of society, especially the village community of Tassel Jaya. And analysis of data used simple linear regression, f test, and Test T. From the results of the research can be seen that the results of the Current Ratio variable test is partially obtained that the < Ttabel Thitung, so that the Current Ratio has not been a significant effect on Return On Assets in the BUMDesa Lancang Kuning village Rumbai Jaya Kempas District, Indragiri Hilir And there is medium relationship between Current Ratio against Return On Assets.